Selección de personal en organizaciones complejas: un caso del equipo de fútbol mexicano para la Copa Mundial 2018 en Rusia - Flegl, Martin; Jiménez-Bandala, Carlos Alberto; Lozano, Carmen; Andrade, Luis (Revista del Centro de Investigación de la Universidad la Salle, 2018)
Selection of personnel in organizations is usually a difficult task. The process gets even more complicated when the selection takes place in complex organizations where different areas can work towards multiple objectives. As many areas might be involved in the selection, the process can become complex and hard to manage. Therefore, it is desirable to use decision-making tools to make the process easier. In this article, we propose new methodology for personnel selection based on Multi-criteria Decision Analysis and the integration of qualitative and quantitative data. We demonstrate the selection process on the case of the Mexican football team selection for the 2018 World Cup in Russia. For the purpose of the article, experts’ opinions are used to evaluate the crucial parameters for the selection.